Assessing the Level of Laboratory Safety Awareness Among Science Education Students - Sumile, Marlowe; Malinao, Rodceal (Journal of Interdisciplinary Perspectives, 2025)
This study examined the level of laboratory safety awareness among Science Education students at Davao del Sur State College in the Philippines. Although science students frequently conduct experiments and practical investigations, there is limited attention to how well they understand and apply laboratory safety practices, which are essential for preventing accidents. To address this gap, the study aimed to measure students’ safety awareness and determine whether it varied across learner groups. A quantitative descriptive research design was employed, and data were collected from 147 BSEd Science students using a modified and validated questionnaire. The results showed that students generally demonstrated a high level of awareness of laboratory rules and procedures. Statistical analyses revealed no significant differences in safety awareness across gender, age, prior laboratory experience, or type of safety training. However, year level was a significant predictor, indicating that safety awareness improves as students progress through the program. These findings highlight the need for continuous, developmentally appropriate safety instruction and for stronger integration of safety practices across all laboratory courses. The study also recommends exploring safety awareness in other disciplines that involve laboratory work to broaden the understanding of safety culture in higher education.